PENGARUH DUKUNGAN ORGANISASI TERHADAP MOTIVASI KERJA DAN KINERJAANGGOTA POLSEK KUTA UTARA - Riantoko, Ronny; Sudibya, Gede Adnyana; Sintaasih, Desak Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Kuta Utara police station is one of the spearheads of public services in any jurisdiction in Badung Police are very important. The existence of highly specialized Kuta Utara police station, judging from the strength member and the characteristics of the region, especially the challenge of duties that require the performance of each individual police officer is a maximum. The performance can be affected by their motivation and support organization perceived by police officers. The purpose of this study were: to analyze the effect on work motivation ogranisasi support, analyze the influence of organizational support to the performance of police officers, and to analyze the influence of motivation on the performance of the police. Popuplasi this research is all Kuta Utara police personnel, as many as 117 people. Data were collected through questionnaires distributed to respondents, and then analyzed using analysis and SEM deskripstif . Menunjukana research results that support organizations and a significant positive effect on the motivation, organizational support positive and significant impact on performance, as well as the motivation of positive and significant impact on performance. The implication of this study is to support the needs of the organization in the implementation of the tasks, then akana enhance work motivation and improve the performance of police officers.
Keywords: Organizational Support, Motivation, Performance